The Relationship Between Trust In Data Security And Low Use Of The JKN Mobile Application Among BPJS Kesehatan Patients At The Siriwini Community Health Center - Sri Wahyuni; Adhi Hilardi; Indra Dewi (CV. AFDIFAL MAJU BERKAH, 2026)
Digital transformation of health services through the Mobile JKN application faces significant adoption challenges in primary healthcare facilities. This study analyzes the relationship between trust in data security and the use of the Mobile JKN application among BPJS Health patients at Siriwini Public Health Center, considering the role of digital literacy as a moderating variable. Using a quantitative approach with a cross-sectional design, this study involved 378 respondents selected through purposive sampling. Data collection used a validated structured questionnaire with a Likert scale, and data analysis employed multiple linear regression and Moderated Regression Analysis. Results show that trust in data security has a significant positive relationship with Mobile JKN application usage (β=0.648; R²=0.360; p=0.000), contributing 36 percent to the variation in application usage. Digital literacy demonstrates a stronger influence with a regression coefficient of 0.723 (R²=0.431; p=0.000), explaining 43.1 percent of the variation in application usage. Moderation analysis reveals that digital literacy strengthens the relationship between trust and application usage (interaction coefficient=0.284; p=0.000), with an additional contribution of 7.7 percent. Findings indicate that low adoption of the Mobile JKN application (62.4 percent never used) is influenced by limited trust in data security systems and digital literacy gaps. Recommendations include strengthening transparency of data security policies, segmented digital literacy improvement programs, and developing interactive tutorial features in the application to facilitate digital health technology adoption in primary healthcare facilities.